Stowarzyszenie społeczne ?Kreator?= ?Kreator? Social Society - Wywiał, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The ?Kreator? Social Society is a non-governmental organization founded in 2002 with a ?social benefit organization? status. It operates mainly in the Lubuskie region, initiating and conducting all sorts of activities addressed to all age groups and important from the social point of view.
Keywords: województwo lubuskie; Stowarzyszenie społeczne "Kreator"; stowarzyszenia; społeczność lokalna